Fresno County Tax Collector Office Staff - Watkins, Howard::::::::: (1987)
Randy Lajoie seated at his desk reading Continuing Education of the Bar (CEB) book on Debt Collection Practice volume 2; on desk: vertical file holder, adding machine, corded push-button telephone, stapled, tape dispenser, flip day calendar, manual typewriter with return lever